2021
DOI: 10.3389/fnut.2021.667643
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Soymilk Fermented by Lactobacillus plantarum HFY01 on D-Galactose-Induced Premature Aging Mouse Model

Abstract: The antioxidant effect of soymilk fermented by Lactobacillus plantarum HFY01 (screened from yak yogurt) was investigated on mice with premature aging induced by D-galactose. In vitro antioxidant results showed that L. plantarum HFY01-fermented soymilk (LP-HFY01-DR) had better ability to scavenge the free radicals 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) diammonium salt (ABTS) than unfermented soymilk and Lactobacillus bulgaricus-fermented soymilk. Histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Recently, the antioxidant and anti-inflammatory effects of the nutrients in plant-based food have attracted extensive attention (46, 47). Fermented soymilk prepared with Lactobacillus plantarum HFY01 and Lactobacillus fermentum CQPC04 exhibits good antioxidant activity, and can significantly improve D-galactose induced premature senescence in mice (11,12). Yang et al (40) also found that fermented soymilk could significantly improve the antioxidant capacity of hyperlipidemia rats, and reduce the arteriosclerosis index and coronary risk index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the antioxidant and anti-inflammatory effects of the nutrients in plant-based food have attracted extensive attention (46, 47). Fermented soymilk prepared with Lactobacillus plantarum HFY01 and Lactobacillus fermentum CQPC04 exhibits good antioxidant activity, and can significantly improve D-galactose induced premature senescence in mice (11,12). Yang et al (40) also found that fermented soymilk could significantly improve the antioxidant capacity of hyperlipidemia rats, and reduce the arteriosclerosis index and coronary risk index.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al ( 14) also found that Lactobacillus casei 16 fermented soymilk has a protective effect against the oxidative damage in HepG2 cells, which may be related to the increase in the content of total phenols and free amino acids. Fermented soymilk can also remarkably enhance the antioxidant capacity of prematurely aging mice and hyperlipidemic rats (11,12,40).…”
Section: In Vitro Antioxidative E Ects Of Soymilk and Fermented Soymilkmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain showed a remarkable upregulation of the transcriptional level of antioxidant-related enzyme genes, such as thioredoxin reductase (TR3), glutathione peroxidase (Gpx1), peroxiredoxin1 (Prdx1), and glutathione reductase (Gsr) encoding genes in the liver (Table 1 ). L. fermentum HFY06, isolated from yogurt obtained from the yak in China, inhibited atrophy of kidneys, brain, spleen, and liver and enhanced serum MDA, GSH, SOD, and CAT levels in D-galactose-induced male Kunming mice (Li et al 2021a , b ). It has also been found that L. fermentum HFY06 is potent in alleviating D-galactose-induced aging in mice, owing to activation of the Nrf2 signaling pathway and enhancement of antioxidant enzymes and levels of downstream regulatory inflammatory factors.…”
Section: Lactobacillus Sp Role In Ameliorating D-galactose-i...mentioning
confidence: 99%
“…In other reports, fermented soymilk from Lactobacillus plantarum HFY01 was demonstrated to protect the liver, spleen, and skin and has potency to decrease inflammation. Oxidative damage D-galactose treated Kunming female mice (Li et al 2021a , b ). Elsewhere, it was revealed that the component isoflavones, genistein, daidzein, glycitein, daidzin, and glycitin are responsible for anti-oxidative activities.…”
Section: Lactobacillus Sp Role In Ameliorating D-galactose-i...mentioning
confidence: 99%